2013
DOI: 10.1097/mol.0b013e32835b4645
|View full text |Cite
|
Sign up to set email alerts
|

The role of dietary protein in blood pressure regulation

Abstract: Increasing dietary protein intake or decreasing carbohydrate intake within reasonable limits may be beneficial for BP. The most and least beneficial protein sources still need to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 51 publications
1
25
0
2
Order By: Relevance
“…Several recent meta-analyses and systematic reviews of randomized controlled trials have also supported a blood pressure-lowering effect of dietary protein intake, reaching similar conclusions [19, 21••, 22, 29•]. Increased protein intake significantly reduced blood pressure compared to carbohydrates, but there was no significant difference in blood pressure reduction between animal and vegetable protein sources.…”
Section: Macronutrientsmentioning
confidence: 73%
See 3 more Smart Citations
“…Several recent meta-analyses and systematic reviews of randomized controlled trials have also supported a blood pressure-lowering effect of dietary protein intake, reaching similar conclusions [19, 21••, 22, 29•]. Increased protein intake significantly reduced blood pressure compared to carbohydrates, but there was no significant difference in blood pressure reduction between animal and vegetable protein sources.…”
Section: Macronutrientsmentioning
confidence: 73%
“…Since the publication of the OmniHeart study, which showed a decrease in both systolic and diastolic blood pressure when protein was substituted for dietary carbohydrate [11], additional large randomized controlled trials of protein supplementation have been published [28••, 29•], which strongly support the inverse relationship between dietary protein and blood pressure. In a 4-week parallel-group randomized clinical trial on the effects of protein supplementation on blood pressure, 60 g/ day of protein (30 % egg protein, 30 % milk protein, 20 % soy protein, 20 % pea protein) reduced systolic blood pressure by 4.9 mmHg ( p =0.005) and diastolic blood pressure by 2.7 mmHg ( p =0.05), as compared to 60 g/day of maltodextrin, among 99 overweight men and women with pre-hypertension or untreated stage I hypertension [29•].…”
Section: Macronutrientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among dietary factors, carbohydrates, sodium are risk factors for hypertension, and animal protein, riboflavin, niacin, calcium, phosphorus, zinc, magnesium, potassium, animal iron [18], potassium [19] are protective factors for hypertension. In the reasonable range dietary protein intake increased or carbohydrate decreased may help control blood pressure [20]. Dietary fiber may play an important role in reducing glycated hemoglobin levels [21].…”
Section: Discussionmentioning
confidence: 99%